ПРОЄКТ «БЕЗПЕЧНЕ МІСТО» ЯК ІНСТРУМЕНТ ДЕРЖАВНОГО УПРАВЛІННЯ У СФЕРІ ЗАБЕЗПЕЧЕННЯ НАЦІОНАЛЬНОЇ БЕЗПЕКИ УКРАЇНИ - Олексій ПУСТОВІТ (Herald of Khmelnytskyi National University. Economic sciences, 2026)
The article examines the theoretical and public administration foundations of the Safe City project as a modern instrument for ensuring public and national security in Ukraine amid digital transformation and an increasingly complex security environment. It is substantiated that the development of digital technologies, intelligent video surveillance, information and analytical systems, and automated data processing leads to a gradual transformation of the project’s functional purpose: from a local tool for recording offenses and monitoring public spaces into an integrated mechanism for threat detection, risk assessment, interagency coordination, and information support for public management decision-making. The theoretical and methodological framework of the study is based on Barry Buzan’s security concept, particularly his ideas concerning the relationship between individual and state security, the multilevel nature of the security environment, and the interrelation between threats and vulnerabilities. Buzan’s work separately addresses individual security, the state as an object of security, and the nature of threats, providing an appropriate theoretical framework for analysing contemporary digital security systems. The main functions of the Safe City project within the public administration system are identified as monitoring, analytical, preventive, coordination, and managerial functions. The study substantiates the need for a transition from a reactive to a preventive and analytical security model, in which digital technologies are used not only to record threats that have already materialised but also to facilitate their early detection and reduce the vulnerability of security objects. An original definition of the Safe City project as an integrated organisational and technological instrument of public administration in the security sphere is proposed. A three-level model of its functioning has been developed, encompassing individual security, the security of territorial communities and public spaces, and the national security of the state. It is determined that the interaction between these levels should be ensured through a unified information and analytical framework aimed at transforming collected data into specific management decisions. Particular attention is paid to the need to maintain a balance between expanding the state’s digital capabilities in the security sphere, personal data protection, privacy, and respect for human rights.